Prove that \([ \cos^{-1} \circ \cos ] (x) = [\cos \circ \cos^{-1}] (x) \) find the value of \(x\).

Prove that \([ \cos^{-1} \circ \cos ] (x) = [\cos \circ \cos^{-1}] (x) \) find the value of \(x\).

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewest\(cos(cos^{-1}x)= x\) for \(x\in[-1,1]\)

& \(cos^{-1}(cosx)=x\) for \(x\in[0,\pi]\)

So \(cos(cos^{-1}x)=cos^{-1}(cosx)\) only \(x\in[0,1]\) – Yash Dev Lamba · 1 year, 3 months ago

Log in to reply